Causal relationship between gut microbiota and thyroid nodules: a bidirectional two-sample Mendelian randomization study - Yan, Shaoshuai; He, Jiawei; Yu, Xudong; Shang, Jianwei; Zhang, Yaosheng; Bai, Han; Zhu, Xingyu; Xie, Xiaoming; Lee, Leanne (Frontiers in Endocrinology, 2024)
Objective: Emerging evidence suggests alterations in gut microbiota (GM) composition following thyroid nodules (TNs) development, yet the causal relationship remains unclear. Utilizing Mendelian Randomization (MR), this study aims to elucidate the causal dynamics between GM and TNs.Methods: Employing summary statistics from the MiBioGen consortium (n=18,340) and FinnGen consortium (1,634 TNs cases, 263,704 controls), we conducted univariable and multivariable MR analyses to explore the GM-TNs association. Techniques including inverse variance weighted, MR-Egger regression, weighted median, and MR-PRESSO were utilized for causal inference.Instrumental variable heterogeneity was assessed through Cochran's Q statistic and leave-one-out analysis. Reverse MR was applied for taxa showing significant forward MR associations, with multivariate adjustments for confounders.